Milton Santos: concepções de geografia, espaço e território - Silva, Sueli Santos da (2009)
Described in this text about the definitions of geography, space and territory in Milton Santos, from the second half of the 1970s, the renewal situation, continuing from 1980 and 1990, when it is necessary to deal with a its main elements - the territory in order to represent its composition, location, formation and evolution. Through the works for a new geography (1978), Space and Society (1979), Thinking space man (1982), Space and Method (1985), Metamorphosis of living space (1988), globalization and fragmentation Territory (1994), The nature of space (1996), Brazil - territory and society in the XXI century (2001), we studied the concepts of space and territory. Thus it is intended to make the analysis of the works and understand the evolution of these concepts in the literary life of Milton Santos.